2020
DOI: 10.1111/1755-6724.14557
|View full text |Cite
|
Sign up to set email alerts
|

Eocene Basins on the SE Tibetan Plateau: Markers of Minor Offset along the Xuelongshan–Diancangshan–Ailaoshan Structural System

Abstract: The offset of geological bodies provides robust evidence of displacement along a fault or ductile shear zone. The amount of displacement along the Xuelongshan–Diancangshan–Ailaoshan structural system, southeastern Tibetan Plateau, is uncertain because of the lack of offset geological markers. This NNW–SSE‐trending system is developed in three isolated metamorphic complexes and interjacent nonmetamorphosed rocks. They are expected to record similar post‐Eocene strain, although their structural patterns should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…U‒Pb ages of CS‐SZ are available through (Akciz et al., 2008; Zhang et al., 2010, 2012; Tang, Yin, et al., 2013; Song et al., 2010; Chen et al., 2022; and this study). U‒Pb ages of Ailaoshan–Red River shear zone are available through (Cao, Liu, et al., 2011; Cao et al., 2009, 2010, 2012; He et al., 2019, 2020; Li et al., 2021, 2022; Liao et al., 2020; Liu, Wang, et al., 2015; Liu et al., 2013, 2020; Qi et al., 2014; Tang, Liu, et al., 2013; Wang, Cao, et al., 2022; Wang et al., 2019; Zhang et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…U‒Pb ages of CS‐SZ are available through (Akciz et al., 2008; Zhang et al., 2010, 2012; Tang, Yin, et al., 2013; Song et al., 2010; Chen et al., 2022; and this study). U‒Pb ages of Ailaoshan–Red River shear zone are available through (Cao, Liu, et al., 2011; Cao et al., 2009, 2010, 2012; He et al., 2019, 2020; Li et al., 2021, 2022; Liao et al., 2020; Liu, Wang, et al., 2015; Liu et al., 2013, 2020; Qi et al., 2014; Tang, Liu, et al., 2013; Wang, Cao, et al., 2022; Wang et al., 2019; Zhang et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The Cenozoic basins were previously assigned a Miocene age based entirely on biostratigrapic and lithostratigrapic correlation [47]. New geochronological data [35][36][37][67][68][69][70][71][72][73] demonstrate that many of them, such as the Nangqian, Laxiu, Mankang, Gongjue, and Jianchuan basins (Figure 1), in the regions eastern of the EHS, developed during the Eocene. They are mostly filled by coarse-grained reddish sandstones with numerous pebble-horizons and minor volcanic intercalations that formed in a contractional setting during 51-34 Ma.…”
Section: A New Cenozoic Tectonic Divisionmentioning
confidence: 99%
“…The vast Miocene lake-basins did not extend into the SE Tibetan Plateau where, alternatively, numerous isolated, small-scale, transpressional basins are preserved in synclinal troughs in the footwalls of reverse faults of limited throw. Their fillings are mainly coarse-grained reddish conglomerates (e.g., [73,77]).…”
Section: A New Cenozoic Tectonic Divisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous Cenozoic potassic-ultrapotassic rocks have been identified on the Tibetan Plateau and its southeastern margin, which provide geological records of the India-Eurasia collision/subduction (e.g., Mo et al, 1993;Chung et al, 2005;Deng et al, 2014;Guo and Wilson, 2019;Dong et al, 2022). Given their geodynamic implications, much geochronological, geochemical and zircon Hf-O isotopic data have been published on them (e.g., Ding et al, 2016;Wang et al, 2018Wang et al, , 2022Tong et al, 2019;Liao et al, 2020;Shen et al, 2021;Chen et al, 2022;Li et al, 2022;Liu et al, 2023). These data demonstrated that each potassic-ultrapotassic body in SE Tibet appears to be unique, and no single petrogenetic model can be universally applied to them.…”
Section: Introductionmentioning
confidence: 99%